Psychosomatic health and cost of home care in care givers - IIJIMA, Kenichi; YAMASHITA, Kazuya (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 1996)
Psychosomatic health conditions and the cost of care were examined in 22 families tendering the sick and provided with visiting nurse services. To evaluate the state of psychosomatic health and the cost of care, the General Health Questionnaire (GHQ) and the Cost of Care Index (CCI, Kosberg et al.) were used. The results of the GHQ showed that factors relating to somatic symptoms, anxiety and sleep disturbance, and social dysfunction are significantly correlated with calculated CCIs. However, activitis of daily living scores of the patients were not correlated with GHQ findings or CCIs. Also, there was no relationship between GHQ results and CCIs and duration of care or the types of care that givers. The GHQ results also revealed elements of social dysfunction in families of a single care giver are marked significantly higher than in those of two or more care givers. There was no correlation between subjects who were given welfare services and those who were not. These data suggested that we should give more attention to the aspect of health and the cost of care in care givers.